Engineering geological studies for empirical design of tunnel 7 of Jakarta - Bandung high-speed railway, Indonesia - Pramono Riski (EDP Sciences, 2021)
The empirical design of tunnel 7 of the Jakarta-Bandung high-speed railway was based on the Basic Quality (BQ) system, which was the Chinese standard of rock mass classification. Due to the high uncertainty of a rock mass classification, comparative studies of rock mass quality and tunnel support systems based on other rock mass classifications are commonly required. The main objective of this research was to assess the rock mass quality and excavatability at the tunnel construction site and propose the tunnel support system based on three widely used methods, namely GSI, RMR, and Q-system. This study involved geological mapping, determination of surface and subsurface rock weathering, rock mass classification of drilling cores, and laboratory testing. The results show that the tunnel construction area consists of highly weathered volcanic and sedimentary rocks. The tunnel elevation consists of poor and extremely to very poor rock masses of sedimentary rocks. Hard digging is the optimum rock mass excavation method to use. Applications of rock bolt, wire mesh, and shotcrete are proposed for the tunnel support system.